A spectrum of pathological changes induced by SARS-COV-2: An observational study in a cohort of pregnant women from Mizoram, India - Vanremmawii; Lalrinfela; Harvey Vanlalpeka; Lalduhchhungi; Zothansangi; Hmingthanzuali Ralte (BMJ Publishing Group, 2023)
Background: Maternal infection by SARS-CoV-2 may lead to adverse pregnancy outcomes and causes pathological changes in the placenta. However, consensus regarding characteristic pathological features is lacking. Researchof the placental histopathology in a cohort of women from Mizoram, India, was conducted to relate the SARS-CoV-2 infection's effectswith pregnancy and its outcome. Materials and methods: The characteristics of 72 pregnant women diagnosed positive for SARS-CoV-2 who eventually delivered at Zoram Medical College Hospital, Mizoram, neonates' well-being, and histopathological features of placentas were studied. Results: Of 72 women in this study, 59 (81.9%) gave birth at full term. Among these births, 5 were normal vaginal deliveries, while the remaining 67 (93.1%) were delivered via cesarean section. The reasons for cesarean delivery were either related to SARS-CoV-2 infection (n ​= ​49), existing obstetric problems (n ​= ​15) or fetal-distress (n ​= ​5). All deliveries resulted in live births of COVID-negative babies, with 80.6% (n ​= ​58) of the newborns having a birth weight of over 2.5 ​kg. APGAR scores ranged from 4 to 6 in 61 (84.7%) of the babies, and 10 neonates required resuscitation, of which 8 were managed in the neonatal intensive care unit (NICU). The placental histopathology showed increased fibrin thrombi in 8 cases (11.1%), while 20 cases (28%) showed focal infarction, microcalcification levels were elevated in 16 cases (22.2%), and a small percentage of cases (1.4%) exhibited small fibrotic villi and inter-villus agglutination. Placental chorioangiosis was detected in 28 (38.9%) of the cases, while avascular villi were seen in 6 cases. Meconium-stained liquor was observed in a single case. Intervillous hemorrhage was found in 42 cases, whileintervillous inflammation and increased syncytial knots were present in 14 and 5 cases, respectively. The placenta pathology of 10 neonates who required resuscitation/NICU admission was not significantly different from that of the 62 neonates who did not require it. However, a higher proportion of placenta from the asymptomatic group showed no abnormality compared to the symptomatic group (p ​= ​0.046). Conclusion: SARS-CoV-2 infection causes a range of morphological changes and lesions in the placenta, including chorangiosis, villositis, chorioamnionitis, fetal vascular malperfusion/thrombosis, fibrin-deposition, increased syncytial-knotting, increased microcalcification, increased villous agglutination, focal infarct, intervilloushemorrhage as well as inflammation. Placental histopathological findings from this study can provide additional information to the existing literature on the subject.